Review of the Development of Handicrafts During the Second Five Year Plan - Planning Commission (Planning Commission, 1956)
The All India Handicrafts Board was established in November, 1952 to study the problems confronting the development and the progress of handicrafts, to advise Government generally on the solution of these problem; and in particular to improve and develop production techniques and new designs to suit the changing conditions, and to promote marketing in India and abroad. The Board was also required as a technical body to advise the Government on grants and loans to be given to State Governments, private organisations and institutes for financing activities necessary for the development and improvement of handicrafts.
Handicrafts Board